Discovery of a new marker to identify myeloid cells associated with metastatic breast tumours - Ansooya A. Bokil; Mathieu Le Boulvais Børkja; Camilla Wolowczyk; Apsana Lamsal; Wenche S. Prestvik; Unni Nonstad; Kristine Pettersen; Sonja B. Andersen; Anna M. Bofin; Geir Bjørkøy; Sjoerd Hak; Miriam S. Giambelluca (Cancer Cell International, 2023)
Abstract Background Myeloid cells play an essential role in cancer metastasis. The phenotypic diversity of these cells during cancer development has attracted great interest; however, their functional heterogeneity and plasticity have limited their role as prognostic markers and therapeutic targets. Methods To identify markers associated with myeloid cells in metastatic tumours, we compared transcriptomic data from immune cells sorted from metastatic and non-metastatic mammary tumours grown in BALB/cJ mice. To assess the translational relevance of our in vivo findings, we assessed human breast cancer biopsies and evaluated the association between arginase 1 protein expression in breast cancer tissues with tumour characteristics and patient outcomes. Results Among the differentially expressed genes, arginase 1 (ARG1) showed a unique expression pattern in tumour-infiltrating myeloid cells that correlated with the metastatic capacity of the tumour. Even though ARG1-positive cells were found almost exclusively inside the metastatic tumour, ARG1 protein was also present in the plasma. In human breast cancer biopsies, the presence of ARG1-positive cells was strongly correlated with high-grade proliferating tumours, poor prognosis, and low survival. Conclusion Our findings highlight the potential use of ARG1-positive myeloid cells as an independent prognostic marker to evaluate the risk of metastasis in breast cancer patients. Graphical Abstract